Determinan Pertumbuhan Ekonomi Wilayah Pengembangan Jawa Barat Tahun 2014-2018 dengan Pendekatan Regresi Panel Spasial - Dian Noviyanti (Seminar Nasional Official Statistics, 2021)
Regional development is an effort to achieve balanced development by fulfilling development potentials according to the various regional/regional capacities. The concept of development with a regional dimension in West Java Province is applied through the division of six development areas (WP). Aspects that affect the economic growth of each WP need to be known as the basis for formulating a development strategy. This study aims to analyze the factors that influence the economic development of West Java WP. Data analysis of this study used the Geographically Weighted Panel Regression (GWPR) method. The determinants of economic growth were examined using the independent variable (X): agricultural GRDP (gross regional domestic product), gross fixed capital formation (PMTB), average length of schooling (RLS), and number of puskesmas. The final result of the study shows that the factors that influence the economic growth of each WP are: agricultural GRDP, PMTB, RLS, puskesmas (WP Bodebekpunjur); Agricultural GRDP, PMTB, puskesmas (WP Purwasuka), agricultural GRDP, PMTB (WP Ciayumajakuning, Priatim-Pangandaran, KK Bandung Basin), and agricultural GRDP, PMTB, RLS (WP Sukabumi).